Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption